2004
DOI: 10.1021/ja0488939
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Tunneling in the Ring Expansion of Noradamantylchlorocarbene

Abstract: Irradiation of 3-(3-noradamantyl)-3-chlorodiazirine produced the corresponding noradamantylchlorocarbene, which could be detected in solution with laser flash photolysis via its pyridinium ylide, and in N2 or Ar matrixes at 9 K with IR and UV/vis spectroscopy. At ambient temperatures, or on irradiation in the cryogenic matrixes, the carbene rearranged to 2-chloro-1-adamantene, which could be trapped in solution and which was characterized by IR and UV/vis at low temperatures. In the dark at 9 K, the carbene al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 16 publications
5
61
0
1
Order By: Relevance
“…6 Experimental evidence, which supports the prediction that tunneling should play an important role in the ring-opening reaction of cyclopropylcarbinyl radical at low temperatures, 7 has very recently been obtained by James and Singleton. 8 In this communication, we report the results of calculations that predict tunneling by carbon should allow the Cope rearrangement of semibullvalene (1, Scheme 1) to occur rapidly at cryogenic temperatures.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…6 Experimental evidence, which supports the prediction that tunneling should play an important role in the ring-opening reaction of cyclopropylcarbinyl radical at low temperatures, 7 has very recently been obtained by James and Singleton. 8 In this communication, we report the results of calculations that predict tunneling by carbon should allow the Cope rearrangement of semibullvalene (1, Scheme 1) to occur rapidly at cryogenic temperatures.…”
supporting
confidence: 70%
“…1 However, even more important than the low barrier height for facilitating tunneling in the degenerate rearrangement of 1 is the narrowness of the reaction barrier. [1][2][3][4][5][6][7] In breaking the cyclopropane ring bond, the distance between the carbons that form this bond increases by only about 0.86 Å.…”
mentioning
confidence: 99%
“…27 Indeed, the structure and reactivity of an impressive range of carbene systems have been probed with this method. [26][27][28][29][30][31][32][33] Relevant to the current report, the first direct observation of hydroxymethylene (HCOH) was reported by Schreiner and co-workers via the pyrolysis of glyoxylic acid followed by the isolation of the pyrolysate in an 11 K Argon matrix. 34 It was discovered that HCOH rearranges to formaldehyde with a half-life of only 2 h by hydrogen tunneling, akin to Sheridan and co-workers' earlier observation of carbon tunneling in matrix isolated 1-methylcyclobutylfluorocarbene.…”
Section: Introductionmentioning
confidence: 59%
“…This result nicely shows the impact of the shape of potential energy barriers,inparticular the length of reaction paths on tunneling. Thec oncept that the barrier width determines the tunneling probability led to Schreiners formulation of tunneling control of chemical reactions: [26,147] whereas the concepts of thermodynamic control (the lowest-energy products will be formed after along time) and kinetic control (the reaction with the lowest barrier happens first) are widespread, tunneling determines the selectivity at low temperatures.F urther examples of tunneling control are found in the ring expansion of noradamantylcarbenes: [148,149] different substituents change the reactivity at cryogenic temperatures and suppress tunneling or lead to different products. [149,150] Theq uestion if the [1,2] Hshift to the alkene or to the corresponding aldehyde takes place preferentially in different hydroxymethylcarbene analogues was answered computationally.This study concluded that the tunneling path length is the decisive quantity.…”
Section: Barrier Widthmentioning
confidence: 99%